'Dissolving Boundaries' – An Analysis of Threshold Concepts Within Disability Theology. Issue 2 (2nd July 2016) - Duke, Zachariah; Mudge, Peter
Abstract : This article focuses on an analysis of threshold concepts (TCs) within disability theology. It explores a range of ideas linked to TCs and the experience of people living with a disability (people LWD). The world in which Christian parishioners encounter people LWD (the focus of this article), could be described as a 'liquid world' which is fuzzy, uncertain, unstable and marked by 'dissolving boundaries' (Barnett, R. 2012. "The Coming of the Ecological Learner." In Transitions and Transformations in Learning and Education, edited by P. Tynjälä, M.-L. Stenström and M. Saarnivaara, 9–20. Dordrecht, NL: Springer) The authors argue that, despite such boundaries, or perhaps because of them, certain thresholds need to be crossed by members of faith communities in order for a person LWD to feel as if he/she genuinely belongs to a community. Nevertheless it is acknowledged that some people involved might be both people LWD and parishioners. The three interrelated thresholds examined within this article are — empowerment, hospitality and neighbourliness. The article links these thresholds with TC theory, and also addresses two related topics — a definition of disability within the discipline of theology, and Jesus as the model for threshold crossing within the Christian tradition. Reflections on TCs in this article are deliberately grounded in the most recent collection of TC theory from Land, R., J. H. F. Meyer and M. T. Flanagan, editors. (2016. Threshold Concepts in Practice . Rotterdam, NL: Sense). Finally, the article considers some relevant, practical responses which, it is argued, members of Christian faith communities ought to consider, so that people LWD feel that they genuinely belong to that particular community. It concludes with a summary of key insights and some possible future research directions.